Soybean LEC2 Regulates Subsets of Genes Involved in Controlling the Biosynthesis and Catabolism of Seed Storage Substances and Seed Development - Manan, Sehrish; Ahmad, Muhammad Z.; Zhang, Gaoyang; Chen, Beibei; Haq, Basir U.; Yang, Jihong; Zhao, Jian (Frontiers in Plant Science, 2017)
Soybean is an important oilseed crop and major dietary protein resource, yet the molecular processes and regulatory mechanisms involved in biosynthesis of seed storage substances are not fully understood. The B3 domain transcription factor (TF) LEC2 essentially regulates embryo development and seed maturation in other plants, but is not functionally characterized in soybean. Here, we characterize the function of a soybean LEC2 homolog, GmLEC2a, in regulating carbohydrate catabolism, triacylglycerol (TAG) biosynthesis, and seed development. The experimental analysis showed that GmLEC2a complemented Arabidopsis atlec2 mutant defects in seedling development and TAG accumulation. Over-expression of GmLEC2a in Arabidopsis seeds increased the TAG contents by 34% and the composition of long chain fatty acids by 4% relative to the control seeds. Transcriptome analysis showed that ectopic expression of GmLEC2a in soybean hairy roots up-regulated several sets of downstream TF genes GmLEC1, GmFUS3, GmABI3, GmDof11 and GmWRI1 that regulate the seed development and production of seed storage substances. GmLEC2a regulated the lipid transporter genes and oil body protein gene OLEOSIN (OLE1). The genes involved in carbohydrate biosynthesis and storage, such as sucrose synthesis, and catabolism of TAG, such as lipases in GmLEC2a hairy roots were down-regulated. GmLEC2a targeted metabolic genes for seed protein in soybean.